In Vivo Validation of Volume Flow Measurements of Pulsatile Flow Using a Clinical Ultrasound System and Matrix Array Transducer. - Hudson, John M.; Williams, Ross; Milot, Laurent; Wei, Qifeng; Jago, James; Burns, Peter N. (Ultrasound in Medicine & Biology, 2017)
The goal of this study was to evaluate the accuracy of a non-invasive C-plane Doppler estimation of pulsatile blood flow in the lower abdominal vessels of a porcine model. Doppler ultrasound measurements from a matrix array transducer system were compared with invasive volume flow measurements made on the same vessels with a surgically implanted ultrasonic transit-time flow probe. For volume flow rates ranging from 60 to 750 mL/min, agreement was very good, with a Pearson correlation coefficient of 0.97 (p < 0.0001) and a mean bias of -4.2%. The combination of 2-D matrix array technology and fast processing gives this Doppler method clinical potential, as many of the user- and system-dependent parameters of previous methods, including explicit vessel angle and diameter measurements, are eliminated.